INTERPRETATION OF PROMOTIONAL MESSAGES IN TIKTOK LIVE STREAMING: CONSUMER RECEPTION OF GLAD2GLOW - Qolbidiasih, Miftahul Nurul; Putranto, Teguh Dwi; Prasetyo, Dwi; Firmannandya, Ade (STIE Mahardhika, 2026)
The use of live streaming on TikTok as a digital media is currently one of the most in-demand communication strategies among business actors across industries, including the beauty industry. This research aims to examine how consumers interpret promotional messages in TikTok Glad2Glow live streams, drawing on Stuart Hall's concept of meaning. In addition, this research will also be examined through the Elaboration Likelihood Model (ELM) perspective. This research employs a qualitative approach with a reception analysis method, through in-depth interviews with informants aged 18-35 who have watched TikTok Glad2Glow live streaming and purchased its products. The results show that consumers have diverse reactions. Two informants are in a dominant-hegemonic position, tend to accept the message as a whole and positively, and process messages through peripheral channels. Meanwhile, three informants are in a negotiated position, which tends to follow a varied message-processing path, as they accept some messages but adjust others. No consumers were found in the oppositional position, because, in general, the messages conveyed could be accepted by consumers, even though several points were not agreed upon and could still be considered.